Microbial landscape of wounds in patients with combat trauma of extremities - Bubman L.I.; Topolyanskaya S.V.; Rachina S.A.; Gladkih M.A.; Usova T.V.; Karpov V.V.; Molochnikov A.Yu.; Nechaev A.I.; Khan S.O.; Emomadov A.M.; Zakharov N.S.; Kharchenko E.I.; et al. (Клиническая микробиология и антимикробная химиотерапия)
Objective.